MEDIA PEMBELAJARAN DALAM MENGHADAPI DI ERA SOCIETY 5.0 - Muh Zuhdy Hamzah; Muhamad Alfi Khoiruman (Universitas Pahlawan Tuanku Tambusai, 2022)
The rapid changes in science and technology require us to be ready to face changes in the world, especially in the field of education. Society 5.0 is a human being who can solve various challenges and social problems by utilizing various innovations born in the era of the industrial revolution 4.0 and centered on technology. Society 5.0 is a development of the industrial revolution 4.0. The data analysis technique used is the Miles & Huberman method with an interactive model. In addition, data collection is obtained from the review process of scientific journals obtained from literature such as scientific journals, books, essays, and other print media that are in accordance with the topic being studied. Learning media that can be developed in preparing educators to face the challenges of the era of society 5.0 is to prepare learning media to make new innovations in utilizing technology as a learning medium. To realize or prepare for society 5.0 in the field of education, it is not enough for students to only understand or be given theory. Instilling ways of thinking to familiarize students in adapting in the future. Keywords: Learning Media, Era Society 5.0